2007
DOI: 10.1002/jbm.a.31518
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of bioactive magnetic nanoparticles: Natural and acquired antibodies

Abstract: Uniform magnetic nanoparticles (MNP) were prepared by nucleation followed by controlled growth of maghemite thin films onto porcine gelatin nuclei. The formed gelatin containing MNP (Gel-MNP) were then coated with dextran (Gel-MNP-Dex) followed by human serum albumin (Gel-MNP-Dex-HSA). Since these MNP are designated for clinical applications, studies concerning the immunogenicity of their antigenic components (porcine gelatin, dextran, and HSA) have been performed in BALB-C mice. These studies demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 34 publications
0
40
0
1
Order By: Relevance
“…10,40 Figure 1 describes the general scheme through which the physical conjugation of thrombin and the physical and covalent conjugation of bFGF onto the surface of the γ-Fe 2 O 3 nanoparticles were performed. Figure 1 illustrates that the covalent conjugation of bFGF to the γ-Fe 2 O 3 nanoparticles is based on the presence of gelatin thin layer on the surface of these nanoparticles, as shown in Figure 2A and B and described previously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,40 Figure 1 describes the general scheme through which the physical conjugation of thrombin and the physical and covalent conjugation of bFGF onto the surface of the γ-Fe 2 O 3 nanoparticles were performed. Figure 1 illustrates that the covalent conjugation of bFGF to the γ-Fe 2 O 3 nanoparticles is based on the presence of gelatin thin layer on the surface of these nanoparticles, as shown in Figure 2A and B and described previously.…”
Section: Resultsmentioning
confidence: 99%
“…10,40 Briefly, 240 mg of gelatin were dissolved in 80 mL of water at 60°C. Then, 160 µL of a Fe +2 solution (10 mmol in 5 mL of 0.1 N HCl) and 57.6 µL of a sodium nitrite solution (7.27 mmol in 5 mL H 2 O) were added to the shaken gelatin solution.…”
Section: Synthesis Of γ-Fe 2 O 3 Nanoparticlesmentioning
confidence: 99%
“…NIR fluorescent iron oxide nanoparticles were prepared by a procedure similar to that described in our previous publication for the preparation of nonfluorescent iron oxide nanoparticles, 24 substituting the gelatin for CANIR covalently conjugated with gelatin. Briefly, 2 mg of CANIR was dissolved in 1 mL of water and added to 1 mg of EDC and 2.2 mg of sulfo-NHS dissolved in 1 mL of water.…”
Section: Synthesis Of Nir Fluorescent Io Nanoparticlesmentioning
confidence: 99%
“…[18][19][20][21][22] Previously, a unique type of uniform IO nanoparticles was prepared and characterized in our laboratory. 23,24 These IO nanoparticles were formed by controlled nucleation of IO onto gelatin, dissolved in an aqueous solution, and followed by stepwise growth of thin layers of IO films onto gelatin-IO nuclei. The same IO nanoparticles have been widely investigated in biological applications, and have been shown to be nontoxic.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] In our laboratory, we have developed maghemite (g-Fe 2 O 3 ) magnetic nanoparticles with a narrow size distribution ranging from a few nm up to approximately 100 nm (hydrodynamic size). [17][18][19] These nanoparticles are prepared by nucleation and then growth of thin magnetic g -Fe 2 O 3 layers on gelatin nuclei. Recently, it was shown that the conjugated gelatin is a weak immunogen: intraperitoneal injection of these g-Fe 2 O 3 nanoparticles dispersed in phosphate buffered saline (PBS) or emulsified with Incomplete Freund's Adjuvant (IFA) mineral oil did not increase significantly the acquired anti-gelatin antibody titers above the basal level of naïve mice.…”
mentioning
confidence: 99%